MUNAROH: PENGEMBANGAN MULTIMEDIA KOSAKATA BAHASA ARAB DENGAN APLIKASI ISPRING SUITE PADA ANAK USIA DINI (Universitas Negeri Semarang, 2023)
This research is motivated by conditions in the field that lack of learning media, especially for the introduction of Arabic vocabulary for kindergarten / RA children. So far, teachers have only used picture cards and singing as media, but the implementation has not been maximized because the media is not dynamic enough to see the development of technology which is very fast now. The problems studied in this study are (1) how to analyze teacher needs for the MUNAROH (Mufrodat Anak Raudhotul Athfal) Multimedia Arabic Vocabulary Media with the iSpring Suite Application for Kindergarten/RA Children in Semarang, (2) how is the prototype of MUNAROH, and (3) how is expert validation and revision of the MUNAROH (Mufrodat Anak Raudhotul Athfal) media prototype. The type of this research is qualitative and quantitative research (mixed method) with a research and development design(RnD). The results of this study, first the teachers want MUNAROH media for TK/RA children group B. Second, the prototype of MUNAROH (Mufrodat Anak Roudhatul Athfal) is media in the form of educational games designed with a PC application display to make it easier for Kindergarten/RA teachers teach the introduction of Arabic to children in this all-digital pandemic era. Third, the results of expert validation include (1) aspects of the feasibility of content and material, (2) aspects of display, (3) aspects of software engineering, (4) aspects of communication, (5) aspects of audio and, (6) visual aspects. The result of obtaining the average overall score is 335.875. So, this learning method is declared feasible with a good predicate. Then, it can be concluded that the learning media “MUNAROH” is suitable to use.